(untitled) (Andamios, Revista de Investigación Social, 2014)
The article analyzes the relationship between the contemporary and the production criminalized population segments, either by migration or criminal actions. Following the proposals of Giorgio Agamben, shows that the state of emergency and the camp (concentration camp, detention center, preventive detention, etc.), and the production of naked life or nuda vida (here seen as decitizenization), have become the pillars supporting the State as an institution. This can be seen in legislation illegalise cross borders, well as domestic laws that criminalize and produce decitizenization to treat excess population and problematic with laws heavy handed.